Management of Higher Education Institutions in the GCC Countries during the Emergence of COVID-19: A Review of Opportunities, Challenges, and a Way Forward - Al Fadhel, Hessa; Aljalahma, Abdulla; Almuhanadi, Mesfer; Asad, Muzaffar; Sheikh, Umaid (The international journal of learning in higher education, 2022)
This study aims to explore measures taken into consideration by Higher Education Institutions (HEIs) in the Gulf Cooperation Council (GCC) countries in response to COVID-19. The study analyzed publicly available published information and updates on the institutions’ management of COVID-19’s impact and allied literature. The study found that most of the universities were diligent in facing the sudden invasion of the pandemic, primarily focusing on the impact of face-to-face teaching. The study further identified opportunities that have evolved, as well as improvements that have been incorporated into teaching, along with challenges that have been faced by students and faculty members or are yet to be catered to. Hence, to maintain sustainability in the quality of education, the study suggested the increase of training and dependence on technology, ultimately blending learning in higher education for GCC countries.